2016
DOI: 10.1371/journal.pone.0149944
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cognitive and Affective Empathy in Spouses' Support Interactions: An Observational Study

Abstract: The present study examined how support providers’ empathic dispositions (dispositional perspective taking, empathic concern, and personal distress) as well as their situational empathic reactions (interaction-based perspective taking, empathic concern, and personal distress) relate to the provision of spousal support during observed support interactions. Forty-five committed couples provided questionnaire data and participated in two ten-minute social support interactions designed to assess behaviors when part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 40 publications
4
55
0
5
Order By: Relevance
“…These results support the theoretical assumption that understanding one's partner's feelings is an important prerequisite for dyadic coping (Bodenmann, ). Men's CoF did predict the long‐term development of their own supportive dyadic coping as perceived by their female partners, which is a similar effect that previous studies have shown in cross‐sectional data (e.g., Verhofstadt et al, ). Moreover, men's CoF did also predict long‐term intrapersonal changes of their female partner's supportive dyadic coping.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…These results support the theoretical assumption that understanding one's partner's feelings is an important prerequisite for dyadic coping (Bodenmann, ). Men's CoF did predict the long‐term development of their own supportive dyadic coping as perceived by their female partners, which is a similar effect that previous studies have shown in cross‐sectional data (e.g., Verhofstadt et al, ). Moreover, men's CoF did also predict long‐term intrapersonal changes of their female partner's supportive dyadic coping.…”
Section: Discussionsupporting
confidence: 85%
“…Second, we expected that interpersonal differences in CoF prospectively predict intrapersonal changes in supportive dyadic coping as perceived by the other partner such that individuals with higher CoF are better able to maintain high levels of supportive dyadic coping in the long run. Given that empirical evidence on gender differences in the association of CoF and supportive behaviors in couples is sparse and mixed (e.g., Levesque et al, ; Verhofstadt et al, ), we did not have any specific expectations regarding gender effects in this study.…”
Section: Clarity Of Other's Feelingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work on social support (Verhofstadt, Buysse, Ickes, Davis, & Devoldre, 2008;Verhofstadt et al, 2016) has found that empathic accuracy is predictive of better support provision as individuals who are more able to recognize their partner's needs can provide more welcome support to their partner in distress.…”
Section: Empathic Accuracy and Partners' Situational Well-beingmentioning
confidence: 99%
“…Immediately after the post-interaction task both partners individually completed a video-review task similar to that used in other studies (e.g., Ickes, Stinson, Bissonnette, & Garcia, 1990;Verhofstadt et al, 2016). The partners were separated and asked to re-experience and re-live their interaction while they viewed a video of it on a laptop.…”
Section: Dyadic Interaction Paradigmmentioning
confidence: 99%